Study On the Uniformity Aluminum Nitrate Thin Film On 2-Inch Silicon Substrate Prepared by RF Magnetron Sputtering - Abd Aziz, Nurul Syamimi; Nayan, Nafarizal; Azman , Zulkifli; Ahmad , Mohd Yazid; Jahanzeb Khan (Journal of Electronic Voltage and Application, 2023)
Aluminum nitrate (AlN) has attracted the researcher's interest due to its unique properties in the semiconductor material and other high-performance devices. This results in numerous techniques to investigate the uniformity of AlN thin film. The deposition in this study is carried out on an AlN on a 2-inch silicon substrate using a magnetron sputtering technique. The RF magnetron sputtering can also produce better film quality and deposit a wide variety of insulators, metals, alloys and composites. In this study, the AlN film was deposited using the RF magnetron sputtering by using three different parameters for the growth of the AlN on the 2-inch Si substrate for uniformity analysis. The uniformity of AlN thin film includes analyses of  the structural, thickness, topology and surface morphology by using the characterization of X-ray diffraction (XRD), atomic force microscopy (AFM), surface profiler and field emission scanning electron microscopy (FE-SEM). Based on the result from three parameters that have been done, parameter one shows the best results. For the crystalline structure results, the peak (100) AlN indicates the highly textured phases similar to a single crystal, and the cross-section result in FE-SEM shows the homogenous thickness.